Exclusion of SARS-COV-2 From Two Maine Overnight Camps July-August 2020. (25th October 2022) - Kowalsky, Rachel H.; Fine, Susan; Eisenberg, Matthew A.
Abstract: Objectives: Summer camp can positively affect self-esteem and social skills. Most United States summer camps did not open during 2020 because of concerns about severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Our objective is to describe exclusion strategies successfully used by 2 summer camps in Maine. Methods: Before camp arrival, all attendees were asked to quarantine at home for 14 d and perform a daily symptom checklist. Salivary specimens were submitted by mail for SARS-COV-2 PCR testing 4 d before arrival, and again 4 d after arrival. At camp, multiple layers of nonpharmaceutical interventions (NPIs) were used. Results: A total of 717 (96.7%) prospective attendees underwent remotely supervised saliva collection; 4 were positive and did not come to camp. Among the 20 who did not submit a sample, 3 did not come to camp; the other 17 underwent screening and a rapid antigen test for SARS-COV-2 immediately upon arrival and before reporting to communal living spaces; all were negative. All campers and staff were re-tested by salivary polymerase chain reaction 4 d after arrival, and all were negative. Conclusions: We demonstrate that it is possible to safely operate overnight camps during a pandemic, thus supporting the continued physical and socioemotional growth of children, using multiple layers of NPIs.